Evaluation of photoprotective properties of pharmaceutical packaging containing cefuroxime by total hemispherical reflectance analysis - Tomasz Górka; Michał Meisner; Beata Sarecka-Hujar (Annales Academiae Medicae Silesiensis, 2024)
Introduction: Improper protection of an active substance may lead to a loss of its original properties. Many methods can be used to assess the photoprotective properties of drug packaging, including the hemispherical directional reflectance method. The aim of the study is to assess the reflectance value for both the outer and direct packaging containing cefuroxime. Material and methods: Two formulations (Ceroxim and Zinnat) of both expired and unexpired packages were tested with a 410-Solar reflectometer. Three types of measurement areas were analyzed: “white” (white areas of the outer cardboard box), “coloured” (coloured areas of the outer cardboard box) and “blister” (the direct packaging made of aluminium/PVC). Results: The highest reflectance value was found in the 700–1100 nm range for both the unexpired and expired preparations. In the 335–380 nm band, the amount of reflected radiation for the unexpired Ceroxim vs Zinnat packages was as follows: 30% vs 12% from the coloured areas, 39% vs 24% from the white areas and 74% vs 70% from the blisters, respectively. For the expired coloured areas of Ceroxim, the reflectance was significantly higher compared to the unexpired (p < 0.001) in all the spectral bands, except 1700–2500 nm. In contrast, the reflectance of the expired white areas of Ceroxim was higher than the unexpired (p < 0.001) for 480–600 nm, 590–720 nm, 700–1100 nm, and 1700–2500 nm. The blisters of the unexpired Zinnat preparation exhibited greater photoprotective properties than the expired in the 335–380 nm range while the unexpired and expired blisters of Ceroxim did not differ. Conclusions: Based on the reflectance value, blisters and white cardboard packages protect cefuroxime against radiation to a greater extent than coloured packages.